The Impact of the Rising of LVMH - Wan, Yu (Eximia, 2023)
Long linked with exclusivity, glamor, and distinction, luxury has recently undergone a paradigm shift because of the success of LVMH. In addition to dominating its sector, this conglomerate of luxury goods has had a significant influence on society and culture. LVMH has a significant impact on a variety of topics, including globalization, the environment, and the world of fashion. We will examine the different ways that LVMH has influenced society and culture in this dissertation, concentrating on two important strands: cultural influence and globalization. Through an examination of LVMH’s association with high culture, its collaborations with artists and celebrities, and its role in preserving cultural heritage, we will consider the company’s impact on culture. We will also explore LVMH’s expansion into various regions, its contribution to the globalization of culture, and the controversies it has faced, including cultural appropriation and poor labor practices. By examining LVMH’s impact and influence, we hope to shed light on the complex and multifaceted role of luxury goods in society today.